The adventures of Tom Sawyer - Twain, Mark, 1835-1910.; McKay, Donald, 1895-1974 (New York : Grosset & Dunlap, 1994)
The adventures of a mischievous young boy and his friends growing up in a Mississippi River town in the nineteenth century.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist, August 1997.
Wilson's Children, November 1996.
Wilson's Junior High School, September 1995.
Keywords: Boys -- Missouri -- Juvenile fiction; Sawyer, Tom (Fictitious character) -- Juvenile fiction; Boys -- Fiction; Sawyer, Tom (Fictional character) -- Fiction; Mississippi River -- Fiction; Missouri -- Fiction; Mississippi River -- Fiction; Missouri -- Fiction; Missouri -- Fiction; Adventure stories; Humorous stories